2019
DOI: 10.1029/2019ef001228
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Sequential Modeling and Predication of Global Land Use and Land Cover Changes by Integrating a Global Change Assessment Model and Cellular Automata

Abstract: Characterizing land use and land cover change (LUCC) is critical for understanding the interaction between human activities and global environmental changes, such as in biological diversity and the carbon cycle. Both natural cycles and human activities can be better examined with more accurate sources of land use data with higher spatial resolution. More importantly, it is crucial to consider spatial heterogeneity to simulate future changes in LUCC. In this paper, a modeling strategy (hereinafter referred to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
5
30
0
1
Order By: Relevance
“…The results in this study are consistent with the global trend reported by Cao et al (2019b) showing increases in agricultural land from 2010 to 2100 in all three scenarios used. The report further shows shrinking in the areas under forest, grassland and shrubland.…”
Section: Future Land Use/cover Changessupporting
confidence: 91%
See 1 more Smart Citation
“…The results in this study are consistent with the global trend reported by Cao et al (2019b) showing increases in agricultural land from 2010 to 2100 in all three scenarios used. The report further shows shrinking in the areas under forest, grassland and shrubland.…”
Section: Future Land Use/cover Changessupporting
confidence: 91%
“…Food production and ecological systems are chiefly affected by changes in cultivated land (Cao et al 2019b). In this study, despite the expansion in agricultural land, it is not reflected in the production of the selected staple food crops (Figure 8).…”
Section: Implication Of Land-use Changes To Staple Food Production In the Regionmentioning
confidence: 71%
“…CA models are spatially explicit and land use change decisions are made based on the state of the neighbouring cells . CA models are often used for the spatial allocation of land use and land cover at a high spatial resolution (Cao et al, 2019) and may be used in combination with other models, such as ABM (e.g. Charif et al, 2017;Mustafa et al, 2017;Troost et al, 2015;Vermeiren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular-based models consider both spatial and temporal components of LULC dynamics [33]. They are easy to standardize and competent to simulate wetland complexes [34]. These have been extensively used for past LULC trend analyses.…”
Section: Introductionmentioning
confidence: 99%